Human adipose glycerol flux is regulated by a pH gate in AQP10. Issue 1 (December 2018) - Gotfryd, Kamil; Mósca, Andreia; Missel, Julie; Truelsen, Sigurd; Wang, Kaituo; Spulber, Mariana; Krabbe, Simon; Hélix-Nielsen, Claus; Laforenza, Umberto; Soveral, Graça; Pedersen, Per; Gourdon, Pontus
Abstract Obesity is a major threat to global health and metabolically associated with glycerol homeostasis. Here we demonstrate that in human adipocytes, the decreased pH observed during lipolysis (fat burning) correlates with increased glycerol release and stimulation of aquaglyceroporin AQP10. The crystal structure of human AQP10 determined at 2.3 Å resolution unveils the molecular basis for pH modulation—an exceptionally wide selectivity (ar/R) filter and a unique cytoplasmic gate. Structural and functional (in vitro and in vivo) analyses disclose a glycerol-specific pH-dependence and pinpoint pore-lining His80 as the pH-sensor. Molecular dynamics simulations indicate how gate opening is achieved. These findings unravel a unique type of aquaporin regulation important for controlling body fat mass. Thus, targeting the cytoplasmic gate to induce constitutive glycerol secretion may offer an attractive option for treating obesity and related complications. Uptake and release of glycerol from the small intestine and adipocytes is facilitated by a subclass of aquaporins (AQP), but how glycerol flow is regulated remains poorly understood. Here authors solve the crystal structure of AQP10 and show how lipolysis is coupled to AQP10 regulation in